Masseteric cysticercosis: an uncommon appearance diagnosed on ultrasound - Vinod Vijay Chander; Sridevi Koduri; Atul Kaushik; Manpreet Kalra; Renu Tanwar; Sukeerat Mann (Revista Sul-Brasileira de Odontologia, 2015)
Cysticercosis occurs when man is infested by the larvae of Taenia solium. Cysticercosis involving the maxillofacial region is not only an uncommon event, but also represents a difficulty in clinical diagnosis. Objective: The present manuscript highlights masseteric cysticercosis as a differential diagnosis of chronic maxillofacial swellings and the role of high resolution sonography as an important noninvasive and non-ionizing imaging modality. Case report: We present a case of masseteric cysticercosis in an eight year old Indian boy, its clinical features, the imaging modalities required and adequate management of the case. Conclusion: Cysticercosis should always be a part of the differential diagnosis of maxillofacial swellings. A thorough case history, clinical examination, proper investigations and conservative treatment forms the mainstay for management of affected patients.